1983
DOI: 10.1136/oem.40.4.413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of occupational exposure to elemental mercury on short term memory.

Abstract: the STM capacity should also be adversely affected by exposure to mercury. This study was conducted to test this prediction and to provide converging evidence that one locus of the neurotoxic effect of mercury is short term memory.Two alternative measures of STM capacity were evaluated under field study conditions. The first, the Wechsler digit span forward,6 was included because it is the test of STM span that has traditionally been used in behavioural toxicology studies.7A second, more extensive test of STM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
3
4

Year Published

1992
1992
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 5 publications
3
30
3
4
Order By: Relevance
“…It could therefore be a random finding. Still, several studies on cussently exposed populations have reported reduced performance on memory tests (9,10,14,18), and the possibility cannot be excluded that the observed poorer performance on the word pairs test among the workers with the highest exposure intensity was real.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It could therefore be a random finding. Still, several studies on cussently exposed populations have reported reduced performance on memory tests (9,10,14,18), and the possibility cannot be excluded that the observed poorer performance on the word pairs test among the workers with the highest exposure intensity was real.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have reported neurobehavioral effects related to motor and cognitive functions (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in humans during ongoing exposure to mercury vapors. Contrary to the large number of studies on currently exposed workers, few epidemiologic studies have focused on the long-term effects on workers who are no longer exposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on current exposure of workers to mercury [57][58][59][60][61][62][63][64][65][66][67][68][69] were mostly conducted on workers in industry (chlorine-alkaline factories, thermometer factories, mercury extraction plants), and in one case on gold miners in the Philippines who use large amounts of mercury without any protection [59]. Correlations between the amount of Hg excreted in urine and measures of cognitive abilities (memory tests, attention span) were always significant and negative, i.e., the more mercury excreted the worse the test results.…”
Section: Mercury Exposure In Workersmentioning
confidence: 99%
“…Achados de estudos observacionais com trabalhadores industriais (produção de lâm-padas fl uorescentes, termômetros ou cloro-álcalis) comparados com controles mostraram défi cit de memória operativa (Smith, Langolf, & Goldberg, 1983), memória verbal de curto prazo (Soleo, Urbano, Petrera, & Ambrosi, 1990), atenção concentrada, habilidade para cálculos (Liang, Sunn, Chen, & Li,1993), lentidão psicomotora (Lucchini et al, 2003, Piikivi, Hanninen, Martelin, & Mantere, 1984, tempo de reação diminuído e incoordenação motora (Lucchini et al, 2003). Foram encontradas correlações entre índice de exposição ao vapor de mercúrio (concentração urinária do metal) e défi cits de atenção e memória visual de curto prazo (Ellingsen et al, 2001), funções executivas e memória (Piikivi et al, 1984), além de lentidão psicomotora (Ellingsen et al, 2001).…”
Section: Avaliação Neuropsicológica De Indivíduos Intoxicados Por Vapunclassified